Impact of soy isoflavones on the prevention and treatment of obesity - Wąsik, Karolina; Tomaszuk, Sebastian; Wojtuś, Magda (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Currently, as the frequency of obesity is alarming, the role of many factors that could contribute in preventing and treating this condition are being researched, among them the certain food with beneficial health profiles - one of them is soybeans, specifically the isoflavones it contains. Populations that consume soy are known for lower risk of various disorders - among them obesity. The aim of this paper is to summarize the existing paper about the role of these bioactive components in the treatment of this condition. The search was conducted using PubMed and Google Scholarship databases. Brief description of the state of knowledge: Obesity is one of the leading challenges in today’s healthcare as it leads to various chronic diseases that are fraught in consequences. Current knowledge is pointing into the association between composition of the soy isoflavones and the lower risk of obesity. Results of the studies indicate that patients affected with obesity could benefit from introducing soy isoflavones into their diet along with other necessary modifications. Conclusions: Soy isoflavones are potential agents in the holistic obesity treatment. Consumption of isoflavones merits further recognition as foregoing results of conducted studies are pointing to its possibly meaningful role. It is worth mentioning that consumption of soy isoflavones is not only an anti-obese factor, but also presents various other health benefits and when consumed rationally poses no risk to human’s well being. We conclude that further studies would enable us to fully reveal the potential of those polyphenols.